"You'll Get Used to It": alterity in Jean Rhys' Voyage in the Dark - Faja, Hiba Meteab; Ruzy Suliza Hashim; Amrah Abdul Majid (Penerbit Universiti Kebangsaan Malaysia, 2020)
Due to the complex intersecting parameters of identity, race, class, and history of Jean Rhys’ writing life, her works allow for interpretation from various disciplines. Rhys' writings reveal the realities of people caught in the complexity of such a web. Her 1934 novel Voyage in the Dark provides insights into the life of Anna Morgan, the heroine of this novel who moves from her home in Dominica to England to face the entire psychological and social struggle by her journey that ends her up with destruction caused by the challenges that seem to conspire to her tragic fate. In understanding the life of Anna Morgan, the woman who has been told that she will “get used” to her circumstances, the concept of alterity is a useful reading approach in unveiling the push and pull factors that drive her to her downfall. As a concept, alterity is explained in this paper through making overt the structure of the novel that exposes various factors that markedly contain facets of alterity such as alienation, assimilation, and separation. By appropriating this reading lens, we hope to show how multiple factors machinate to show the systematic ways in which Anna Morgan’s fate is sealed when the heroine herself and others around her cannot accept otherness and fusion.